A partire da Egon Kunz: una teoria male interpretata (Altre Modernità, 2022)
Starting from Egon Kunz's theory, known as pushpull theory, the essay aims to investigate the misinterpretation that has been given to it, stiffening the descriptive taxonomy that makes a distinction between asylum seekers and economic migrants. This division schematically presents a complex and articulated phenomenon, based on a discretionary distribution, bordering on the arbitrary, since the migratory drive is not reducible to a single factor, but appears as a combination of different factors. This has led to the need for a review of the push-pull approach, which has also led to a strict interpretation at a legal level.
Keywords: Egon Kunz, pushpull theory, economic migration, refugees